Working Together to Carry Water: Research Ethics when One of Two Parents is Indigenous - Tuladhar-Douglas, Will; Tuladhar-Douglas, Bhavana (Ethnobiology Letters, 2018)
What are the ethical challenges and opportunities for a household where one parent is Indigenous and the other not? This article uses events from one family history to explore how social and political contexts in both the country of Indigenous origin and the country of residence drive research ethics. It argues that research ethics for such parents should be framed within the ethics of transmitting Indigenous culture for the family within a transnational Indigenous lineage.